DESIGN AND ANALYSIS OF HYBRID RECTENNA FOR RF ENERGY HARVESTING APPLICATIONS - KAMARUZAMAN, NUR ELISYA SYAHIRAH (IRC, 2019)
The improvisation and growing of wireless communication devices increase the problem of their energy autonomy. The dc powering of abandoned sensors or sensor nodes localized in areas which are risky or inconvenient are a sample of application. The other method to prevent typical power source inside the building is wireless energy transmission. In this paper, it is specifically focus on the conversion of the microwaves at dual band frequency which is 1.8 GHz and 2.1 GHz. Because of the location of the frequency band at 4G communication band, cheaper maintenance and technology and small attenuation through atmosphere, the frequency is largely being used. An antenna to collect the microwave incident power and a rectifier circuit, it completes the structure of the rectenna. The rectifier will convert RF energy sources into useful DC power and it has a nonlinear characteristic. Rectifier consists of an input HF filter, an output bypass capacitor, Schottky diodes and resistive load. Harmonics from the diode will be rejected by the input HF filter which is a low pass filter. Other than that, it is also as a matching circuit between the antenna and the rectifying circuit. This low pass filter can be directly included on the radiating element by using harmonic-rejecting antennas. In conclusion, rectenna can be a great equipment to supply inspiring new harvesting technology with good innovation and improvisation.